Global Value Chains, Firm Preferences and the Design of Preferential Trade Agreements. (27th November 2018) - Eckhardt, Jappe; Lee, Kelley
Abstract: The conventional view in the literature is that only the largest and most productive firms in a country benefit, and hence support the signing of preferential trade agreements (PTAs), as they are able to take advantage of the key benefits such agreements offer. In this paper we argue that such firms may indeed be generally supportive of PTAs, but that their preferences often differ when it comes to the exact design of PTAs. These different preferences stem from the ways that firms have organized their value chains. We focus on one crucial issue where firms may hold different preferences, depending on the organization of their value chains: Rules of Origin (RoO). We test the plausibility of our argument through a detailed analysis of the preferences and political strategies of tobacco firms in the context of the North American Free Trade Agreement (NAFTA) negotiations. Abstract : Whether or not firms source the bulk of their inputs from PTA partner countries affects their preferences on RoO provisions.